2G Ethanol Production From Palm Lignocellulosic Biomass - Carvalho, Leonard Guimaraes; Modesto, Luiz Felipe A.; Aranda, Donato A. Gomes; Jr, Nei Pereira (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Brazil presents the world's largest potential for the production of palm oil due to nearly 75 million hectares of land suitable for palm culture and advantageous soil and climate. The biomass generated in the production of palm oil (palm pressed fiber, PPF) is mainly composed of lignocellulosic material that can be hydrolyzed into fermentable sugars for further conversion to ethanol. This work evaluated alkaline pretreatment of this palm oil residue and subsequent Simultaneous Saccharification and Fermentation (SSF), achieving a conversion of glucose to ethanol higher than 90% and a concentration equivalent to 22.40 g/L of the alcohol.